Sequencing batch membrane photobioreactor for simultaneous cultivation of aquaculture feed and polishing of real secondary effluent. (June 2019) - Lau, Allen K.S.; Bilad, M.R.; Osman, N.B.; Marbelia, L.; Putra, Z.A.; Nordin, N.A.H.M.; Wirzal, M.D.H.; Jaafar, J.; Khan, Asim L.
Graphical abstract: Highlights: Sequencing batch membrane photobioreactors (SB-MPBRs) were studied. Secondary effluent was used to cultivate Staurastrum sp.. Low phosphorous offers higher biomass production coupled with higher membrane fouling. Too low HRT resulted in a low nutrients removal. Abstract: Microalgae technology is attractive for simultaneously treating wastewater and producing valuable biomass. However, biofuel application demands a very low net-energy input that can hardly be fulfilled. Therefore, exploration of a more direct-use of microalgae biomass and selection of appropriate microalgae species are necessary to fine-tune viable applications. This study assesses performance of sequencing batch membrane photobioreactors (SB-MPBRs) for simultaneously polishing secondary effluent by cultivating Staurastrum sp., a species suitable as aquaculture feed. The effect of feed composition (high and low phosphorous, P) on microalgae growth, membrane fouling propensity, nutrient removal, as well as oxygen enrichment capacity were evaluated. Overall results demonstrate the effectiveness of SB-MPBR to cultivate Staurastrum sp. in secondary effluent by achieving biomass concentration of 0.45 and 0.6 g/L and very low nutrients concentrations in the effluents (≈ 0, 10 and 2 mg/L, for chemical oxygen demand (COD), TN and TP respectively). The actual biomass productivity of the SM-MPBRS are 40.0 and 30.0 g/(day m 3 ) for the low-P and high-P feeds, corresponding to production costs of 11.3 and 15.1 $/kg biomass, respectively. Low-P feed results in a slightly higher biomass productivity of 33% compare to high-P feed, but slightly higher fouling propensity. The growth in both SB-MPBRS seems to be limited by the inorganic carbon supply. Too-short HRT leads to nutrients accumulation of the nutrients and eventually reduced their removal efficiencies. Overall results show a new cultivation method for aquaculture feed while at the same time polish secondary effluent and enrich its oxygen concentration.